Beyond Legal Frameworks: Uncovering the Hidden Impact of Gender Violence in Indonesia’s 2024 Political Recruitment - Lestari, Puji; Niravita, Aprila; Arditama, Erisandi; Suran Ningsih, Ayup; Munandar, Moh. Aris; binti Jamil @ Osman, Zuraini (Jurnal Suara Hukum, 2025)
The violent dynamics of gender, power, and politics synergistically undermine the political recruitment participation of women in Indonesia. Victims are often unaware of the oppressive power structures disguised as social norms, which continue to marginalize women's roles in politics. This research aims to identify the types of discrimination faced by women during the recruitment process for the 2024 legislative elections and to analyze the effectiveness of existing legal regulations in eliminating these obstacles. The study employs a normative doctrinal research approach by analyzing legislation, policies, and recruitment documents related to gender-based political representation. The analysis is further supported by theoretical frameworks concerning symbolic violence and gendered power relations. The study finds that systematic discrimination is perpetrated through “invisible” power structures that maintain a gap between formal legal protections and actual societal practices. Although the law provides a constitutional quota of 30% for women’s representation, symbolic and structural violence continues to suppress meaningful political participation. Legal frameworks tend to emphasize procedural equality, thereby failing to eliminate entrenched discriminatory practices. The study advocates for regulatory reforms that go beyond formal equality to ensure substantive and meaningful political inclusion of women in Indonesia. Keywords: Gender discrimination; Political recruitment; Symbolic violence.